(untitled) (Sebha University Conference Proceedings, 2025)
This study aimed to identify the current state of the quality of course instruction in the Department of Educational and Psychological Sciences at the Faculty of Education, Tripoli, from the perspective of female students. To achieve this objective, the descriptive method was employed by collecting data from female students using an electronic questionnaire form prepared by the College’s Department of Quality Assurance and Performance Evaluation, due to its high reliability in measuring what it was designed to assess. The questionnaire consisted of 63 items distributed across four domains, with some domains merged to balance the number of items. The questionnaire was distributed to a sample of 116 female students. After analyzing the responses using the Statistical Package for the Social Sciences (SPSS), version 22, the researcher reached the following results: The overall quality of course instruction across all domains was rated as high, with a mean score of 3.7989. Specifically, the domain of lecturer’s personal qualities ranked first with a high level of quality and a mean score of 4.0132. The domain of instruction and assessment quality ranked second, also at a high level, with a mean score of 3.8123. The domain of research and academic tasks of the lecturer came in third place, with a high level and a mean score of 3.7728. Finally, the domain of course content, organization, and learning resources ranked fourth, yet still received a high-quality rating, with a mean score of 3.6354.